Lanthanoid/Alkali Metal ß-Triketonate Assemblies: A Robust Platform for Efficient NIR Emitters. - Reid, Brodie; Stagni, S.; Malicka, J.; Cocchi, M.; Sobolev, A.; Skelton, B.; Moore, E.; Hanan, G.; Ogden, Mark; Massi, Massimiliano (2015)
The reaction of hydrated lanthanoid chlorides with tribenzoylmethane and an alkali metal hydroxide consistently resulted in the crystallization of neutral tetranuclear assemblies with the general formula [Ln(Ae⋅HOEt)(L)4]2 (Ln=Eu3+, Er3+, Yb3+; Ae=Na+, K+, Rb+). Analysis of the crystal structures of these species revealed a coordination geometry that varied from a slightly distorted square antiprism to a slightly distorted triangular dodecahedron, with the specific geometrical shape being dependent on the degree of lattice solvation and identity of the alkali metal. The near-infrared (NIR)-emitting assemblies of Yb3+ and Er3+ showed remarkably efficient emission, characterized by significantly longer excited-state lifetimes (τobs≈37–47 μs for Yb3+ and τobs≈4–6 μs for Er3+) when compared with the broader family of lanthanoid β-diketonate species, even in the case of perfluorination of the ligands. The Eu3+ assemblies show bright red emission and a luminescence performance (τobs≈0.5 ms, equation image≈35–37 %, ηsens≈68–70 %) more akin to the β-diketonate species. The results highlight that the β-triketonate ligand offers a tunable and facile system for the preparation of efficient NIR emitters without the need for more complicated perfluorination or deuteration synthetic strategies.